Disrupsi Sistem Sosial-Ekologis: Dampak Kebijakan Larangan Pembakaran Lahan Terhadap Komunitas Petani di Kecamatan Mantangai, Kalimantan Tengah - Meilinda, Salsa Rizkia; Yusril, Yusril; Salman, Darmawan; Muhammad, Sawedi (Hasanuddin University, 2025)
This study examines the impact of land burning ban policies on the socio-ecological systems of communities in Mantangai District, Central Kalimantan, focusing on traditional farming systems and their implications for food security, social structures, and ecological sustainability. Using a qualitative approach with case study methods, the research involved 27 informants through in-depth interviews, participant observation, and document analysis. The findings reveal three major transformations: (1) the shift in human-environment relations from an integrated to a fragmented system, (2) the transformation of socio-economic structures from collective to individual, and (3) a food security crisis due to loss of access to traditional farming systems. Through Environmental Sociology and Environmental Justice perspectives, the research demonstrates how policies based on the Human Exemptionalism Paradigm ignore the complexity of community socio-ecological relations that reflect the New Environmental Paradigm. Modernization programs like food estate have failed due to disregarding local knowledge, while criminalization of traditional practices has created systemic environmental injustice. The study recommends policy reformulation that integrates local wisdom and environmental justice to strengthen community socio-ecological resilience.